Canagliflozin, serum magnesium and cardiovascular outcomes—Analysis from the CANVAS Program. Issue 3 (13th March 2021) - Wang, Katherine M.; Li, JingWei; Bhalla, Vivek; Jardine, Meg J.; Neal, Bruce; de Zeeuw, Dick; Fulcher, Greg; Perkovic, Vlado; Mahaffey, Kenneth W.; Chang, Tara I.
Abstract: Background: Patients with type 2 diabetes (T2D) are predisposed to derangements in serum Magnesium (Mg), which may have implications for cardiometabolic events and outcomes. In clinical trials, participants with T2D randomized to sodium‐glucose co‐transporter 2 (SGLT2) inhibitors have shown mild to moderate increases in serum Mg from baseline levels. This post hoc analysis assesses the relation between serum Mg with cardiovascular outcomes in 10, 140 participants of the Canagliflozin Cardiovascular Assessment Study (CANVAS) Program. Methods: We evaluated the association of baseline serum Mg with the primary composite end point of death from cardiovascular causes, non‐fatal myocardial infarction, and non‐fatal stroke, and tested whether this association is modified by baseline serum Mg. Using mediation analysis, we determined whether change in serum Mg post‐randomization mediates the beneficial effect of canagliflozin on cardiovascular outcomes. Results: Mean serum Mg levels at baseline were 0.77 ± 0.09 mmol/L in both canagliflozin group and placebo groups. The canagliflozin group experienced an average increase in serum Mg by 0.07 mmol/L (95% CI, 0.065–0.072 mmol/L; p < .001) for the duration of the trial. We found no association between baseline serum Mg levels and the primary composite end point, and no evidence of effect modification by baseline Mg levels. Change in serum Mg post‐randomization was not a mediator of the effects of canagliflozin on cardiovascular outcomes. Conclusions: In participants of the CANVAS Program, baseline and post‐randomization serum Mg levels are not associated with cardiovascular outcomes. Abstract : In the CANVAS Program, participant baseline serum Mg is not associated with cardiovascular outcomes and does not modify the effect of canagliflozin on cardiovascular outcomes. Canagliflozin‐associated rise in serum Mg levels does not mediate the beneficial effects of canagliflozin on cardiovascular outcomes.